Antiproliferative and Apoptotic Effects of Novel Anti-ROR1 Single-Chain Antibodies in Hematological Malignancies. (April 2017) - Aghebati-Maleki, Leili; Younesi, Vahid; Baradaran, Behzad; Abdolalizadeh, Jalal; Motallebnezhad, Morteza; Nickho, Hamid; Shanehbandi, Dariush; Majidi, Jafar; Yousefi, Mehdi
Receptor tyrosine kinase–like orphan receptor (ROR) proteins are a conserved family of tyrosine kinase receptors that function in developmental processes including cell survival, differentiation, cell migration, cell communication, cell polarity, proliferation, metabolism, and angiogenesis. ROR1 has recently been shown to be expressed in various types of cancer cells but not normal cells. Pharmacokinetics and pharmacodynamics of single-chain Fragment variable (scFv) antibodies provide potential therapeutic advantages over whole antibody molecules. In the present study, scFvs against a specific peptide from the extracellular domain of ROR1 were selected using phage display technology. The selected scFvs were further characterized using polyclonal and monoclonal phage enzyme-linked immunosorbent assay (ELISA), soluble monoclonal ELISA, colony PCR, and sequencing. Antiproliferative and apoptotic effects of selected scFv antibodies were also evaluated in lymphoma and myeloma cancer cell lines using MTT and annexin V/PI assays. The results of ELISA indicated specific reactions of the isolated scFvs against the ROR1 peptide. Colony PCR confirmed the presence of full-length VH and Vκ inserts. The percentages of cell growth after 24 h of treatment of cells with individual scFv revealed that the scFv significantly inhibited the growth of the RPMI8226 and chronic lymphocytic leukemia (CLL) cells in comparison with the untreated cells ( p < 0.05). Interestingly, 24-h treatment with specific scFv induced apoptosis cell death in the RPMI8226 and CLL cells. Taken together, our results demonstrate that targeting of ROR1 using peptide-specific scFv can be an effective immunotherapy strategy in hematological malignancies.